2016
DOI: 10.1016/j.alcohol.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal choline supplementation in a sheep model of first trimester binge alcohol fails to protect against brain volume reductions in peripubertal lambs

Abstract: Fetal alcohol spectrum disorder (FASD) is a leading potentially preventable birth defect. Poor nutrition may contribute to adverse developmental outcomes of prenatal alcohol exposure, and supplementation of essential micronutrients such as choline has shown benefit in rodent models. The sheep model of first-trimester binge alcohol exposure was used in this study to model the dose of maternal choline supplementation used in an ongoing prospective clinical trial involving pregnancies at risk for FASD. Primary ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Volume reductions were shown to be associated with behavioral impairments(Stevens and Haney-Caron, 2012, Chiang et al, 2007). As was observed in the present animal study, reduction of overall brain size of prenatal alcohol exposed subjects has been repeatedly reported in postmortem studies as well as in neuroimaging studies(Wisniewski et al, 1983, Archibald et al, 2001, Birch et al, 2016). In addition to the reduction of overall brain size, the absolute volumes of various brain cortical and subcortical areas were consistently reduced in humans with prenatal exposure to alcohol(Chen et al, 2012, Rajaprakash et al, 2014, Archibald et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…Volume reductions were shown to be associated with behavioral impairments(Stevens and Haney-Caron, 2012, Chiang et al, 2007). As was observed in the present animal study, reduction of overall brain size of prenatal alcohol exposed subjects has been repeatedly reported in postmortem studies as well as in neuroimaging studies(Wisniewski et al, 1983, Archibald et al, 2001, Birch et al, 2016). In addition to the reduction of overall brain size, the absolute volumes of various brain cortical and subcortical areas were consistently reduced in humans with prenatal exposure to alcohol(Chen et al, 2012, Rajaprakash et al, 2014, Archibald et al, 2001).…”
Section: Discussionsupporting
confidence: 88%
“…Measurement of serum choline levels, either pre‐ or postintervention, was not included in any of the rodent preclinical studies. However, serum choline was measured in the sheep trial (Birch et al., ) and was confirmed to be lowered by EtOH compared to controls and increased by choline supplementation. Wozniak and colleagues () confirmed that serum choline levels were raised by the choline intervention, but as all participants had been exposed to alcohol, baseline serum choline levels could not indicate whether there was an underlying deficiency compared to nonexposed individuals.…”
Section: Discussionmentioning
confidence: 94%
“…We included 30 animal studies (mice n = 3 [ 106 , 107 , 108 ]; rats n = 14 [ 43 , 97 , 98 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 ]; guinea pigs n = 4 [ 120 , 121 , 122 , 123 ]; rabbits = 1 [ 124 ]; sheep n = 3 [ 125 , 126 , 127 ]; and cows n = 5 [ 128 , 129 , 130 , 131 , 132 ]) and 6 human studies [ 133 , 134 , 135 , 136 , 137 , 138 ] reporting on fetal growth in response to prenatal methyl donor supplementation. In 16 of these studies, methionine was used [ 43 , 97 , 98 , 115 , 116 , 117 , 118 , 119 , 123 , 124 , …”
Section: Resultsmentioning
confidence: 99%